Structural Analysis Technique and Bad Synchronization Styles - Melnik, D.; Lukashenko, O. (ХНУРЭ, 2009)
This paper discusses early detection of potentially missing synchronizers on clock domain crossing paths, using structural static analysis.
Keywords: clock domain crossing; metastabillity; static verification